Pemberian makanan enteral berformulasi bahan pangan lokal terhadap kadar zat besi dan hemoglobin pada tikus putih (Rattus norvegicus) - Dini Ariani; Mukhamad Angwar; Yuniar Khasanah; Ratnayani Ratnayani; Titin Nuraeni (Jurnal Gizi Klinik Indonesia, 2013)
Background: Enteral nutrition is nutrition used to fulfill the needs of nutrition entirely and as the supplement for malnutrition patient. In a certain condition of a patient, this nutrition is usually given in the form of liquid. Local material foods such as tempeh, rice, mung bean, and ganyong have adequate nutrition, therefore they are suitable for being used as main raw materials in the making of enteral nutrition.Objective: To know the influence of feeding enteral nutrition formulated with local food material toward malnutrition white rats (Rattus norvegicus) of which the parameters are iron (Fe), hemoglobin (Hb) level and weight.Method: This research used Completely Random Design (CRD). Twenty-seven of malnutrition male white rats were divided into 3 groups of treatment with 9 repetitions for each group of the treatment. Group A was given enteral nutrition diet of formula A (tempeh, rice, and mung bean as the main raw material), group B was given enteral nutrition diet of formula B (tempeh, rice, mung bean, and ganyong as the main raw material), and group C (as the positive control) was given commercial enteral nutrition. The daily giving of enteral nutrition is 20 g/day during 30 days. The analysis of Fe and Hb level and the measurement of weight firstly were done before the treatment is given. The next measurement was conducted in 15th day and 31st day. Statistical analysis used ANOVA test dan DMRT of significance 5%.Results: The result showed that the treatment of the enteral nutrition feeding of formula B was more optimal than formula A in terms of the way to increase the level of Hb and Fe. Those two components will give positive effect toward the increasing of the weight of malnutrition white rats (Rattus norvegicus).Conclusion: The enteral nutrition of formula B is more proper to be developed as the main material of making enteral food in order to treat the malnutrition.